2013
DOI: 10.1016/j.jcf.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium avium and Mycobacterium abscessus complex target distinct cystic fibrosis patient subpopulations

Abstract: MAC affects adult patients with a mild form of CF, whereas MABSC affects younger patients with more severe CF and more frequent intravenous antimicrobial treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
84
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 27 publications
(45 reference statements)
4
84
3
Order By: Relevance
“…There is general consensus that, in CF and non-CF populations, M. abscessus is a more virulent bacteria than MAC (13,17,28,29,36), that it may be associated with a greater rate of FEV 1 decline (7,30), and that it is more difficult to treat (17,26,37). However, our results demonstrate that both MAC and M. abscessus can be cleared spontaneously in a subset of patients with CF or can result in an apparently indolent infection.…”
Section: Original Researchmentioning
confidence: 56%
See 1 more Smart Citation
“…There is general consensus that, in CF and non-CF populations, M. abscessus is a more virulent bacteria than MAC (13,17,28,29,36), that it may be associated with a greater rate of FEV 1 decline (7,30), and that it is more difficult to treat (17,26,37). However, our results demonstrate that both MAC and M. abscessus can be cleared spontaneously in a subset of patients with CF or can result in an apparently indolent infection.…”
Section: Original Researchmentioning
confidence: 56%
“…In those who were treated, lung function decline stabilized in the year after therapy initiation even though the organism was often not eradicated. Azithromycin use has recently been shown to block autophagy, suggesting that it has the potential to predispose patients with CF to mycobacterial infection (39), although this effect has not been seen in case-control studies (29,40). In addition, a recent nested case-control study by Binder and colleagues showed that patients with CF with incident NTM infections were less likely to have had chronic azithromycin treatment in the last year (41).…”
Section: Original Researchmentioning
confidence: 99%
“…Nine out of the eighteen CF patients infected with M. abscessus complex bacteria (50%) were also culture positive for Aspergillus (Table 2). Aspergillosis is associated with M. abscessus complex isolation from cystic fibrosis patients in many countries [38][39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…DAG has been shown to activate protein kinase C, which is known to modulate the activation of neutrophils and macrophages (45). This activity further emphasizes the inflammatory response observed in CF lungs and participates in the increased virulence of M. abscessus in CF patients compared to other mycobacteria (46).…”
Section: Discussionmentioning
confidence: 83%